10.01 - Timothy Mathews (Artefilosofia)
This lyric essay is a version of the one in Chronicles of Art and Hope, published later in 2025 by Ma Bibliothèque. This is a collection where in response to more artworks, various forms of writing help me shine various lights on force, on vulnerability, and on ways to reach out without stifling.